Gender-specific effects of oxidative balance score on the prevalence of diabetes in the US population from NHANES - Wu, Cuiling; Ren, Chenxia; Song, Yingda; Gao, Huifang; Pang, Xin; Zhang, Lianyun (Frontiers in Endocrinology, 2023)
Background: The relationship between oxidative balance score (OBS) and diabetes remain poorly understood, which may be gender-specific. We conducted a cross-sectional study to investigate the complex association between OBS and diabetes among US adults. Methods: Overall, 5233 participants were included in this cross-sectional study. The exposure variable was OBS, composed of scores for twenty dietary and lifestyle factors. Multivariable logistic regression, subgroup analysis, and restricted cubic spline (RCS) regression were applied to examine the relationship between OBS and diabetes. Results: Compared to the lowest OBS quartile group (Q1), the multivariable-adjusted odds ratio (OR) (95% confidence interval (CI) for the highest OBS quartile group (Q4) was 0.602 (0.372-0.974) (P for trend = 0.007) and for the highest lifestyle OBS quartile group was 0.386 (0.223-0.667) (P for trend < 0.001). Moreover, gender effects were found between OBS and diabetes (P for interaction = 0.044). RCS showed an inverted U relationship between OBS and diabetes in females (P for nonlinear = 6e-04) and a linear relationship between OBS and diabetes in males. Conclusions: In summary, high OBS was negatively associated with diabetes risk in a gender-dependent manner.